2010
DOI: 10.1038/cgt.2009.84
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of HIF-1α by oncolytic reovirus infection independently of VHL and p53

Abstract: Many oncolytic viruses are currently being tested as potential cancer therapeutic agents. To be effective, these viruses must replicate and propagate efficiently through the tumor mass. However, it is possible that the hypoxia that characterizes many tumors may be an obstacle to viral therapy because of its inhibition of viral replication and propagation. We, therefore, decided to test how oncolytic reovirus and its target cells respond to hypoxia. We found that reovirus infection suppresses hypoxia inducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 37 publications
3
25
1
Order By: Relevance
“…The cytotoxic effects of a number of oncolytic viruses are affected by hypoxia and the level of HIF in the infected cells (Cho et al , 2010; Connor et al , 2004; Hiley et al , 2010). Viral infection itself caused deregulation of HIF levels within hypoxic cancer cells (Gupta-Saraf & Miller, 2014), resulting in the varying regulation of their downstream target genes (Cho et al , 2010). In the present study, we showed that a velogenic NDV infection led to a downregulation of HIF-1α protein in a p53-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic effects of a number of oncolytic viruses are affected by hypoxia and the level of HIF in the infected cells (Cho et al , 2010; Connor et al , 2004; Hiley et al , 2010). Viral infection itself caused deregulation of HIF levels within hypoxic cancer cells (Gupta-Saraf & Miller, 2014), resulting in the varying regulation of their downstream target genes (Cho et al , 2010). In the present study, we showed that a velogenic NDV infection led to a downregulation of HIF-1α protein in a p53-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, activation of the oncogenic Ras-signaling path-way enhances reoviral oncolytic targeting in various types of human cancers (17)(18)(19), although our recent study shows that other signaling pathways may also contribute to the susceptibility of these cancers to reoviral replication and oncolysis (20). In addition, our study first reports that reovirus infection induces down-regulation of hypoxia-inducible factor (HIF)-1· independently of VHL and p53, suggesting that reovirus may be useful as a potential therapeutic agent against chemoresistant or radioresistant tumors that are hypoxic and show increased levels of HIF-1· (21). It has also been reported that reoviral oncolysis was associated with the induction of apoptosis in various cancer types (22).…”
Section: Introductionmentioning
confidence: 79%
“…101 They found that reovirus infection suppresses HIF-1α at the protein level, but not at the messenger RNA level, in colon cancer HCT116 cells under hypoxic conditions. This reduction of HIF-1α is independent of VHL or p53 because it took place in both VHL-/-renal carcinoma A498 and p53-/-HCT116 colorectal cancer cells.…”
Section: Reovirusmentioning
confidence: 99%
“…The authors proposed to use reovirus together with an HIF-1α inhibitor as a potential therapeutic regimen against chemoresistant or radioresistant tumors that are hypoxic with increased levels of HIF-1α. 101 As a result, there appears to be a functional similarity between reovirus and VSV in their sensitivity to elevated levels of HIF-1α. 97,101 EMCV Picornaviruses have been explored as OVs.…”
Section: Reovirusmentioning
confidence: 99%
See 1 more Smart Citation